Observing glacier dynamics with low-cost, multi-GNSS positioning in Victoria Land, Antarctica - Holly Still; Robert Odolinski; M. Hamish Bowman; Christina Hulbe; David J. Prior (Journal of Glaciology)
This study examines the performance of low-cost, low-power GNSS positioning systems for glacier monitoring in high-latitude environments. We compare the positioning performance of co-located low-cost u-blox ZED-F9P GNSS units (a few hundred USDs) and survey-grade Trimble R10 units (> $10,000 USD) under stationary (on land) and dynamic (on glacier) conditions near Terra Nova Bay, Antarctica. Low-cost and survey-grade systems yield almost identical error magnitudes under short (3 m), medium (34 km) and long (390 km) baseline kinematic-positioning scenarios. We further examined the efficacy of low-cost GNSS for glaciological applications by installing four u-blox and two Trimble receivers on Priestley Glacier to observe tide-modulated ice flexure. All receivers successfully detected subtle tidal oscillations with amplitudes < 3 cm, consistent with the predicted phasing from a tide model. These experiments offer a strong rationale for the widespread use of low-cost receivers to expand and densify GNSS monitoring networks, both in Antarctica and in glaciated regions worldwide.